Minat Beli Ulang Ditinjau Dari Kualitas Pelayanan, Gaya Hidup Dan Store Atmosphere (Studi Pada Kenbirti Coffee And Bites Di Sragen) - Yessy Fitria Ningrat (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to determine the Repurchase Interest of Kenbirti Coffee and Bites Customers in Sragen in terms of service quality, lifestyle and store atmosphere. In this study, the authors used a descriptive quantitative approach. The population of consumers of kenbirti coffee and bites in Sragen, the samples used in this study were 100 people. The results of this study have a significant effect both partially and simultaneously between Service Quality, Lifestyle and Store Atmosphere on Repurchase Interest at Kenbirti Coffee And Bites in Sragen. Keywords: Service Quality; Lifestyle; Store Atmosphere; Repurchase Interest.